The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.bpj.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Scale Effects of Lipopolysaccharide Modifications on Bacterial Outer Membrane Defenses

Abstract: Lipopolysaccharides (LPS) are a main constituent of the outer membrane of Gram-negative bacteria. Salmonella enterica, like many other bacterial species, are able to chemically modify the structure of their LPS molecules through the PhoPQ pathway as a defense mechanism against the host immune response. These modifications make the outer membrane more resistant to antimicrobial peptides (AMPs), large lipophilic drugs, and cation depletion, and are crucial for survival within a host organism. It is believed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 77 publications
(99 reference statements)
7
58
0
Order By: Relevance
“…all of the simulations, large-scale bilayer properties were unaffected by binding of LL-37 and largely consistent with previous results, 8 as detailed in Supplementary Results and Table S1.…”
Section: Ll-37 Does Not Affect Bilayer Properties On the Microsecond supporting
confidence: 90%
“…all of the simulations, large-scale bilayer properties were unaffected by binding of LL-37 and largely consistent with previous results, 8 as detailed in Supplementary Results and Table S1.…”
Section: Ll-37 Does Not Affect Bilayer Properties On the Microsecond supporting
confidence: 90%
“…chemotype when the -PO − 4 and -PO 2− 4 cases are compared. Overall, these results indicate that, as hypothesized previously,19 lipid A modifications help stabilize the bilayer structure in the absence of divalent cations and may reduce reliance on these cations for stability.…”
supporting
confidence: 83%
“…Figure S4); this difference was less pronounced in mLPS systems, likely due to the already increased ordering that palmitoylation confers. 19 Finally, increased inter-lipid hydrogen bonding was observed in LPS systems with the reduced phosphate charge, while the change in mLPS systems was not statistically significant for this metric.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The results showed that only 5% of the Xcc LOS molecules are released. In the outer membrane of gram negative bacteria the negatively charged LPS molecules cover most of the outer surface and divalent cations such as Mg 2+ and Ca 2+ are essential to neutralize this negative charge and allow strengthening of the lateral interactions between neighboring LPS molecules, which provides enhanced stability for the external bacterial membrane . Similar electrostatic interactions and effects such as increased hydrogen bonding and tighter lipid packing and cross‐linking exerted by divalent cation bridging can be expected to take place in the pathogen‐mimetic mNP–LOS nanostructures to provide the observed stability.…”
Section: Resultsmentioning
confidence: 99%